PLAY ME: interactive sonification of sexual arousal in long-distance relationships - Arnold Rudolf (Paladyn, 2020)
Music is the best medium for expressing emotions and arousal nonverbally. PLAY ME is a gender-neutral Arduino-based system that allows partners in a long-distance relationship to perceive each other’s sexual arousal and to provide stimulation of erogenous zones using music. PLAY ME’s main parts are a tiny pneumatic anal probe connected to a pressure sensor and a bodysuit with integrated vibrators. Whenever both partners wear these devices, a real-time exchange of emotions and corporeal feelings can be enabled. Three sensors capture genital sexual arousal and transform it into music: a pulse sensor, a sensor for galvanic skin response and a pneumatic anal pressure probe. The anal probe measures pelvic tensions and contractions. Its signal controls the main voice. Higher arousal leads to stronger pelvic muscle tensions. Measured data are mapped to pitch, so the level of sexual arousal is audible in a comprehensive way, and orgasms can be clearly identified by regular pulsating sounds. The pulse sensor and the skin response sensor are the driving rhythm and drone frequency. The vibrators in the bodysuit are controlled by sound that is generated by the partner using any audio source. Mixing the sounds generated by the sensors and the instrument leads to interactive music that can enhance erotic feelings and sexual arousal in the way of biofeedback. This article describes the background and construction of the PLAY ME system and shows diagrams of sensor values recorded during sexual stimulation. After a discussion of the results, there is an outlook toward further development.